Studi Karakteristik Mineral Pirit pada Seam Batubara A2 dan C Di Pit 1 Utara Penambangan Banko Barat PT. Bukit Asam, Tbk, Tanjung Enim, Sumatera Selatan - aufa fikri abdillah; ansosry ansosry; heri prabowo (Departemen Teknik Pertambangan FT UNP, 2021)
PT. Bukit Asam, Tbk is a coal mining company in South Sumatera Province that supplies coal from Steam Power Plant (PLTU) with domestic shipments to Tarahan Steam Power Plant (PLTU) reaching 39.7% of coal production. The purpose of this research is to determine the potential characteristics of pyrite minerals that produce sulfur dioxide gas (SO2) which affects coal combustion and it can form an encrustation or slag in the steam power plant (PLTU) boiler pipes. The results of the XRF analysis for coal of A2 seam detected the oxidation of sulfur SO3 is 41.28% and Fe is 17.908% and XRF detected the oxidation of sulfur SO3 is 75.838% and Fe 8.026% for coal of C seam. Based on the results of microscopic analysis on coal of A2 seam and C seams, there are different of pyrite minerals types analysed. According to the analysis on coal of A2 seam that it contained an epigenetic pyrite mineral type. Mineragraphic analysis on coal of seam C that it contained a sygenetic pyrite mineral type. the framboidal pyrite mineral has fine crystals so it is reactable quickly and it is predicted that it can cause a slag during coal combustion in steam power plants (PLTU).